PERANAN OTOPSI FORENSIK DALAM MENGUNGKAP TINDAK PIDANA PEMBUNUHAN OLEH KEPOLISIAN REPUBLIK INDONESIA - Ely, Sofiah; Simangunsong, Frans (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
A major part of the difficulty in locating or identifying murderers at crime scenes is the inability to identify victims with uncertain probabilities or long-term harm. If the time of the crime is cut or mutilated the body is too far away and the evidence is insufficient because the crime scene witness does not dare to be safe because it results. Autopsy It also helps in the judicial process to prove the crime of murder and to prove the crime of murder. This study uses a pharmacodynamic approach. These findings suggest that the presence of age bias when police report a homicide the certainty of death and the identity of the suspect at autopsy play a role. To determine the victim’s identity